2015
DOI: 10.1007/s00167-015-3741-2
|View full text |Cite
|
Sign up to set email alerts
|

Is PLC repair of a peel-off femoral lesion an effective option in a multiligament setting?

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…In a review by Geeslin et al [14], surgical direct repair was recommended in acute avulsed PT injury. In another study by Bonanzinga et al [3] who directly repaired type 1 and 2 PT peel‐off lesion which was defined as bone avulsion of the main structures of the PLC without any mid‐substance stretch injury or fibula‐based injuries [10], reported a significant reduction of SSD of external rotation from 15° ± 8° to 0° ± 6° and improvement of IKDC form evaluation. Consistent with the present study, another review by Kennedy et al [19] reported that isolated or combined treatments for the avulsed PT of the knee are directly repaired or treated with recess procedure in acute stage (< 3 weeks) after injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review by Geeslin et al [14], surgical direct repair was recommended in acute avulsed PT injury. In another study by Bonanzinga et al [3] who directly repaired type 1 and 2 PT peel‐off lesion which was defined as bone avulsion of the main structures of the PLC without any mid‐substance stretch injury or fibula‐based injuries [10], reported a significant reduction of SSD of external rotation from 15° ± 8° to 0° ± 6° and improvement of IKDC form evaluation. Consistent with the present study, another review by Kennedy et al [19] reported that isolated or combined treatments for the avulsed PT of the knee are directly repaired or treated with recess procedure in acute stage (< 3 weeks) after injury.…”
Section: Discussionmentioning
confidence: 99%
“…A photograph was taken at both initial and final positions. On the photograph, the bilateral tibial external rotation angle was calculated, and the result of the index knee was compared with the contralateral knee [3]. Positive dial test was defined as side‐to‐side difference (SSD) of ER > 10°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…recommended reconstruction of the PLC structures based on their comparative cohort study [ 31 ]. PLC injury sometimes involves femoral peel-off lesions that can be successfully managed with primary repair [ 32 ]. In this series, repair of the PLC structure demonstrated satisfactory results, apparently because they were all repaired in the acute phase, and recent suture anchors could be used.…”
Section: Discussionmentioning
confidence: 99%
“…Bonanzinga ve ark., çoklu bağ yaralanması olan 13 olguda AÇB "peel-off" yaralanmasının primer tamiri ile başarılı sonuçlar bildirmişlerdir. [57] Bağın primer onarımı propriyoseptif özelliklerini korurken, aynı zamanda çoklu bağ cerrahisinde zaten kısıtlı olan greft kaynaklarının da ekonomik olarak kullanımına imkân sağlar. ÖÇB peel-off yaralanması kemik avulsiyonlara göre çok daha nadirdir.…”
Section: Aci̇l Tedavi̇unclassified